Music and the young mind : enhancing brain development and engaging learning - Harris, Maureen, 1956-; MENC, the National Association for Music Education (U.S.) (Lanham : Rowman & Littlefield Education, 2009)
From the Publisher: Written for the early childhood educator-experienced or trainee, musician or nonmusician this book describes a music-enriched environment for teaching the whole child. With easy-to-follow lesson plans, sing-along CDs (sung in a suitable pitch for the young child), and supporting literature, educators can gain musical confidence as they explore research on child development, learn how to create a music-enriched environment and build musical confidence, see a curriculum time-frame, and follow lesson plans with ideas for further musical creativity and exploration
-- List of figures -- Foreword / Susan Kenney -- Acknowledgments -- Introduction -- 1: Brain research and how children learn -- 2: Biology and music-tapping the global rhythm -- 3: Healing -- 4: Gifted children -- 5: Teacher training -- 6: Appropriate curricula -- 7: Multicultural integration -- 8: Year's music curriculum -- 9: Lesson plans of basic concepts -- 10: Resource guide -- 11: Let's get started -- 12: Tomorrow's world -- Appendix A: Songs listed alphabetically -- Action B: Action songs -- Appendix C: Tracks on CDs by lesson plan -- References -- About the author
"Published in partnership with MENC: The National Association for Music Education."
Includes bibliographical references (pages 129-136) and index
Keywords: Preschool music -- Instruction and study; Early childhood education